«Ледачий Джек»: кодування та контекстуалізація опору в жіночих оповідях індіанців Аппалачі - Файн, Е. (Народна творчість та етнологія, 2012)
Elizabeth C. Fine. «Lazy Jack»: Coding and Contextualizing Resistance in Appalachian Women’s Narratives. This article examines the dominant motifs and related versions of tale «Lazy Jack» to appreciate the changes Carter-Sexton has brought to her telling. The author of the article analyzes the implicit coding strategies of appropriation, juxtaposition, and incompetence used by Carter-Sexton to subvert male dominance, and links her coding strategies to those used by other female storytellers in her family. The article explores the metanarrative and meta-performative techniques the author uses to recontextualize the tale.